Sistem Monitoring Kelembapan Tanah Berbasis Internet of Things (IoT) dengan Integrasi Google Spreadsheet dan MIT App Inventor untuk Optimasi Irigasi Tetes pada Perkebunan Palawija - Rouhillah; Rizki Faulianur; Rizki Mumtazi (Politeknik Aceh, 2025)
This research developed a prototype of an Internet of Things (IoT)-based automatic drip irrigation system integrated with Google Sheets and an Android application based on MIT App Inventor. The system utilizes ESP32 and a soil moisture sensor to monitor soil moisture conditions in real-time and automatically control the water pump based on a moisture threshold value. The threshold value is determined by the user through the Android application and stored in Firebase and EEPROM, so the system can continue to operate even if the internet connection is lost. Data on soil moisture, pump status, threshold value, and recording time are recorded periodically every five minutes into a Google Sheet to support data monitoring and analysis. The test results show that the system has a humidity measurement error rate of 2.68%, which indicates that the performance of the sensor and control system is quite accurate and reliable. This system is suitable for application on small to medium-scale agricultural land and has the potential to be further developed with the application of artificial intelligence to improve irrigation efficiency